2011
DOI: 10.4028/www.scientific.net/amr.414.198
|View full text |Cite
|
Sign up to set email alerts
|

Study of Migration of Different Petroleum Hydrocarbon Contaminated Components in Soil

Abstract: This paper is about the migration of the total petroleum hydrocarbon (TPH) contamination, which concludes the migration rule of the TPH contamination through designing indoor soil column leaching experiment. Through researching the migration concentration of different components of TPH, experiment concludes that different components have different relative transfer abilities in typical soil, and the transfer ability has an inverse relation to the molecular weight and the ring numbers of aromatic hydrocarbon. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Some research results showed that crude oil has harmful effects on plant seed germination [2,3]. On the contrary, other studies found that low oil concentration can improve the seed germination and accelerate the seeding growth [4,5]. Therefore, further study should be done in order to clarify the effects of oil pollution on plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some research results showed that crude oil has harmful effects on plant seed germination [2,3]. On the contrary, other studies found that low oil concentration can improve the seed germination and accelerate the seeding growth [4,5]. Therefore, further study should be done in order to clarify the effects of oil pollution on plant growth.…”
Section: Introductionmentioning
confidence: 99%